2006
DOI: 10.1021/es060999b
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of CeO2 Nanoparticles for Escherichia coli. Physico-Chemical Insight of the Cytotoxicity Mechanism

Abstract: The production of nanoparticles (NPs) is increasing rapidly for applications in electronics, chemistry, and biology. This interest is due to the very small size of NPs which provides them with many interesting properties such as rapid diffusion, high specific surface areas, reactivity in liquid or gas phase, and a size close to biomacromolecules. In turn, these extreme abilities might be a problem when considering a potentially uncontrolled exposure to the environment. For instance, nanoparticles might be high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
437
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 745 publications
(490 citation statements)
references
References 25 publications
21
437
1
3
Order By: Relevance
“…Heteroaggregation of NPs with microbial cells such as bacteria and algae is important for fate, transport, transformation, and toxicity of NPs in both aquatic and terrestrial environments [106][107][108][109][110][111][112][113]. Heteroaggregation could occur between a single particle and a cell, or via particle aggregate-cell interactions [114] -with important implications in the natural environment.…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heteroaggregation of NPs with microbial cells such as bacteria and algae is important for fate, transport, transformation, and toxicity of NPs in both aquatic and terrestrial environments [106][107][108][109][110][111][112][113]. Heteroaggregation could occur between a single particle and a cell, or via particle aggregate-cell interactions [114] -with important implications in the natural environment.…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…For instance, NPs-microorganism heteroaggregation can lead to increased removal of NPs from wastewater during secondary treatment [106,[115][116][117][118]. Interactions between cell walls of microorganisms and NPs are also thought to precede uptake and toxicity [107,108,[110][111][112]116,119], and may be important for trophic transfer of NPs in both aquatic and terrestrial environments [108,[119][120][121].…”
Section: Heteroaggregation Between Nanoparticles and Microorganismsmentioning
confidence: 99%
“…Studies on antibacterial activity among the various metal oxides nanoparticles, zinc oxide nanoparticles, have been found to be highly toxic. Many studies have shown that selective toxic nature of ZnONPs toward bacteria shows the minimal effect on human cells, which is suggested their potential uses in agricultural, food industries, diagnostics, surgical devices, and nanomedicine-based antimicrobial agents [21][22][23][24]. Among the several metal oxide nanoparticles, ZnONPs are emerged as booming nanoparticle due to their attractive characteristics and ideal properties in various biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanisms of nanoparticle toxicity against various bacteria are not understood completely. Nanoparticles are able to attach to the membrane of bacteria by electrostatic interaction, and disrupt the integrity of the bacterial membrane (Thill et al 2006). Nanotoxicity is generally triggered by the induction of oxidative stress by free radical formation (Nel et al 2009;Soenen et al 2011).…”
Section: Anti-bacterial Activitymentioning
confidence: 99%